Sirtuin 1 Levels in Recurrent Implantation Failure - Yaprak Engin-Ustun; A. Seval Ozgu-Erdinc; Emel Kiyak Caglayan; Cavidan Gulerman; Esma Sarikaya; Ayla Aktulay; Canan Demirtas; Salim Erkaya; Nafiye Yilmaz (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2017)
Abstract Sirtuin 1 has an important role in cellular processes, including apoptosis and cellular stress. The purpose of this study was to assess serum sirtuin 1 levels in women with recurrent implantation failure (RIF). In this cross-sectional study, we included 28 women with RIF, 29 healthy women who had conceived by in vitro fertilization (IVF), and 30 women with a 1-cycle failure of IVF as controls. Human serum nicotinamide adenine dinucleotide (NAD)-dependent deacetylase sirtuin-1 (SIRT1/SIRT2L1) levels were detected using a commercial colorimetric kit. Recurrent implantation failure patients have higher sirtuin 1 levels than non-pregnant women and healthy pregnant women, but this difference did not reach statistical significance due to the low number of patients in our study. These higher sirtuin 1 levels may result from the inflammation imbalance of RIF patients. The only statistically significant correlation found was between age and sirtuin (r = 0.277, p = 0.009).